Modeling and simulation of a hospital evacuation before a forecasted flood. (March 2015) - Chen, Wanying; Guinet, Alain; Ruiz, Angel
Abstract: As high level emergencies can have serious consequences on hospital activities, an emergency management plan to face a crisis situation must be specified and assessed. Even though more and more research is devoted to this area, most studies are based on academic assumptions and the proposed improvement methods are difficult to apply in the real world. This paper deals with a hospital evacuation plan facing a flood based on a real life scenario. We modeled the evacuation process and identified its different activities. We then used SIMIO–a commercial simulation software–to translate our conceptual model into a dynamic model. Numerical experiments were conducted to determine the best way to assign the resources. We also propose two organizational improvements to the current, as-is, evacuation process. By simulating these changes, we were able to show that, if implemented together, they should be able to reduce the evacuation time by 1 h and 18 min, an improvement of 23.8% with respect to the current average evacuation time.